Factors associated with post-traumatic stress disorder in nurses after directly caring for COVID-19 patients: a cross-sectional study - Hyo-Jeong Yoon; Soon Yeung Bae; Jihyun Baek (BMC, 2023)
Abstract Background Nurses are particularly at risk of suffering from post-traumatic stress disorder (PTSD) owing to their overwhelming workload, risk of infection, and lack of knowledge about the coronavirus disease 2019 (COVID-19). PTSD negatively affects an individual's health, work performance, and patient safety. This study aims to assess factors related to PTSD among nurses after providing direct care to COVID-19 patients. Methods This study is a secondary analysis aimed at identifying factors influencing PTSD among nurses who provided direct care to COVID-19 patients. Data from 168 nurses, collected between October and November 2020, were analyzed. The independent variables were personal, interpersonal, and organizational and COVID-19-related factors (experience of quarantine and direct care of COVID-19 patients), and the dependent variables were PTSD symptoms evaluated based on the PTSD Checklist-5. The nurses' experience of direct care for COVID-19 patients in the designated COVID-19 isolation wards during the first wave of the pandemic (February 2020 to May 2020) was included. Results Among the nurses, 18.5% exhibited symptoms of PTSD. When providing direct care to a patient in the designated COVID-19 isolation ward, nurses witnessing the death of a patient (p = .001), low level of nurse staffing (p = .008), and inconvenience of electronic health records programs (p = .034) were associated with PTSD symptoms. The experience of quarantine owing to COVID-19 was also associated with PTSD symptoms (p = .034). Additionally, the higher the nurse managers' ability, leadership, and support of nurses in the current ward, the higher the possibility of lowering nurses' PTSD symptoms (p = .006). Conclusions Governments and hospitals should prepare and implement organizational intervention programs to improve nurse managers' leadership, nurse staffing levels, and electronic health records programs. Additionally, because nurses who have witnessed the death of a COVID-19 patient or are self-isolating are vulnerable to PTSD, psychological support should be provided.